2016
DOI: 10.1080/00207454.2016.1207172
|View full text |Cite
|
Sign up to set email alerts
|

D-dimers (DD) in CVST

Abstract: D-dimer is elevated in patients with acute/subacute CVST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
2
5
0
8
Order By: Relevance
“…Our study found that DD is elevated in patients with a CVST diagnosis, as other authors have reported [9]. Additionally, we looked into whether an elevated DD concentration is related to a worse course of the disease and its complications.…”
Section: Discussion and Clinical Implicationssupporting
confidence: 66%
See 1 more Smart Citation
“…Our study found that DD is elevated in patients with a CVST diagnosis, as other authors have reported [9]. Additionally, we looked into whether an elevated DD concentration is related to a worse course of the disease and its complications.…”
Section: Discussion and Clinical Implicationssupporting
confidence: 66%
“…It is unclear whether D-dimer (DD) levels reflect clinical presentation, radiological features of CVST involvement, and outcome in this disease. There are some studies showing that DD concentrations are elevated in CVST [9]. DD measurement is useful in patients suspected of CVST, and patients with elevated levels should be urgently sent for venography of CT or MR (depending www.journals.viamedica.pl/neurologia_neurochirurgia_polska Izabela Domitrz et al, D-dimer and cerebral and sinus venous thrombosis on their resolution and sensitivity in a hospital).…”
Section: Introductionmentioning
confidence: 99%
“…We selected acute/subacute patients from our database. Inclusion criteria were as follows: (1) meeting the diagnostic criteria for CVST established by the American Heart Association/American Stroke Association in 2014 8 ; (2) lling defect or obstruction of cerebral sinus in the magnetic resonance venogram, digital subtraction angiography, or operation searching; (3) clinical features such as vomiting, visual disturbances, focal neurologic de cit, seizure, and other typical symptoms; (4) acute and subacute patients whose time from onset to addition was less than 30 days 13,14 , or named non-chronic patients; (5) an initial blood sample for laboratory testing 12 hours of admission. Exclusion criteria were as follows: (1) patients with unrelated other serious brain lesions, serious lung disease, or heart disease; (2) patients with undesirable follow-up, including refusal or loss to follow-up; (3) patients less than 18 years old; (4) patients without complete clinical data; (5) chronic patients whose time from onset to addition was more than 30 days.…”
Section: Patient Selectionmentioning
confidence: 99%
“…Hal ini sesuai dengan literatur bahwa sebagian besar kasus CVST terjadi pada perempuan. 1,[2][3][4][5] Subjek penelitian memiliki rentang usia dari 19-65 tahun. Sebanyak 87,5% subjek penelitian ini terdiagnosis CVST melalui DSA dengan lokasi terbanyak ada di sinus transversus kiri.…”
Section: Pada Penelitian Ini Didapatkan Bahwa 80%unclassified
“…Beberapa penelitian sebelumnya menyebutkan bahwa kadar D-dimer plasma berhubungan dengan diagnosis CVST. [2][3][4][5] Rekomendasi dari American Heart Association (AHA) dan American Stroke Association (ASA) menyebutkan bahwa pasien dengan kadar D-dimer yang tinggi dapat mengindikasikan kemungkinan adanya CVST, dibandingkan dengan nilai D-dimer yang normal. Penelitian yang telah dilakukan di China didapatkan bahwa, pasien yang telah didiagnosis CVST dan memiliki kadar D-dimer yang tinggi memiliki kecenderungan lebih lamanya berkurang gejala dibandingkan dengan yang memiliki kadar D-dimer normal.…”
unclassified